(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the association between the inflammatory factor in the diet and obesity indicators in men with prostate cancer. This is a cross-sectional study using data from 42 men diagnosed with prostate cancer being followed up at the Cancer Institute of Ceará. Food consumption, anthropometric, and body composition data were evaluated. Food consumption was obtained through the application of a food frequency questionnaire. Body mass index (BMI), waist circumference (WC), waist-hip ratio (WHR) and the percentage of body fat (% BF) determined by bioimpedance were obtained. The inflammatory factor of the diet was determined according to a specific protocol. Associations were assessed using Pearson and Spearman tests. Statistical analyzes were performed using SPSS version 20.0 and p values ​​<0.05 were considered to be statistically significant. The sample had an average age of 70.5 ± 7.3 years. Most were overweight (64.3%) and excess body fat (97.6%). In addition, 92.9% had a highly inflammatory diet. No associations were found between the dietary inflammatory factor with BMI (p = 0.763), WC (p = 0.549), WHR (p = 0.137) and% BF (p = 0.733). As a conclusion, we observed that the diet of the evaluated patients was highly inflammatory and although it was not associated with obesity indicators, it signals the poor quality of the diet of the evaluated men.